Frequentist approaches: sample size in adaptive clinical designs - Koyama, Tatsuki (Henry Stewart Talks, 2017)
General concepts of sample size calculation, Group sequential designs, Pocock method, O'Brien-Fleming method, Alpha-spending approach, Adaptive designs, Pre-specification of design components, Conditional probabilities